A new species of Telosma (Apocynaceae, Asclepiadoideae) from Thailand - Rodda, Michele; Poopath, Manop (Phytotaxa, 2019)
The genus Telosma in Thailand includes three species, Telosma cordata, T. pallida and T. puberula. Recent fieldwork at Namtok Phlio National Park and Khao Ang Rue Nai Wildlife Sanctuary led to the collection of a further species that is here described as Telosma thailandica. It is the only Telosma species with gynostegium exceeding the corolla tube.